PENGARUH PEMEKARAN KECAMATAN TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT (Studi Pada Kecamatan Pamatang Sidamanik Kabupaten Simalungun) - Sri Utari Haloho (Universitas Medan Area, 2016)
This study aims to determine how much influence the expansion districts on the socio-economic conditions of people in the District Pamatang Sidamanik. The socio-economic indicators in this study can be seen from the income, education, health and housing. The method used in this research is quantitative. The data obtained by distributing questionnaires to 100 (one hundred) respondents consisting of community. Furthermore, the data that is processed by techniques Product Moment Correlation Test, significant, and the coefficient determinant to see how big the effect of variable X to variable Y.